2015
DOI: 10.1177/0003319715590558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPAP on New Endothelial Dysfunction Marker, Endocan, in People With Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) is associated with increased cardiovascular (CV) morbidity and mortality. Endocan is a surrogate endothelial dysfunction marker that may be associated with CV risk factors. In this study, we tested whether serum endocan is a biomarker for OSA. Serum endocan levels were measured at baseline in 40 patients with OSA and 40 healthy controls and after 3 months of continuous positive airway pressure (CPAP) treatment in the patients with OSA. All participants were evaluated by full polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 53 publications
0
54
0
5
Order By: Relevance
“…Based on the association of obstructive sleep apnea (OSA) and endothelial dysfunction, endocan was also very recently investigated in a prospective study by Altintas et al74 The effect of the condition on the molecule’s levels was assessed in moderate-to-severe OSA patients, at baseline and following 3 months of continuous positive airway pressure treatment. According to the results, not only was endocan able to distinguish patients with OSA from individuals with suspected, though not confirmed, diagnosis but also further correlated with the severity of the condition, measured by the apnea-hypopnea index and the therapeutic response.…”
Section: Endocan and The Respiratory Systemmentioning
confidence: 99%
“…Based on the association of obstructive sleep apnea (OSA) and endothelial dysfunction, endocan was also very recently investigated in a prospective study by Altintas et al74 The effect of the condition on the molecule’s levels was assessed in moderate-to-severe OSA patients, at baseline and following 3 months of continuous positive airway pressure treatment. According to the results, not only was endocan able to distinguish patients with OSA from individuals with suspected, though not confirmed, diagnosis but also further correlated with the severity of the condition, measured by the apnea-hypopnea index and the therapeutic response.…”
Section: Endocan and The Respiratory Systemmentioning
confidence: 99%
“…Also, were inversely correlated with eGFR and this value influenced, independently of traditional and non-traditional risk factors, all-cause mortality and CVD events in 251 CKD patients. Multiple linear regression with serum endocan as the dependent variable showed that endocan levels had a significant and independent correlation with cIMT and FMD in patients with OSA [35]. …”
mentioning
confidence: 93%
“…Kundi et al demonstrated that endocan levels were significantly correlated with Syntax score and high-sensitive C-reactive protein (30) . In another study, endocan levels were found to be correlated with carotid intima media thickness and flow mediated dilation in obstructive sleep apnea patients (31) . All these studies suggest and support the possible association of endocan with inflammation and atherogenesis, but our findings are different.…”
Section: Discussionmentioning
confidence: 93%